1992
DOI: 10.1111/j.1476-5381.1992.tb14348.x
|View full text |Cite
|
Sign up to set email alerts
|

CP‐93,129, sumatriptan, dihydroergotamine block c‐fos expression within rat trigeminal nucleus caudalis caused by chemical stimulation of the meninges

Abstract: 1 The effects of intravenously administered 5-HTIB receptor agonists were examined on c-fos-like immunoreactivity, an indicator of neuronal activation, within the brain stem. C-fos was induced by injecting an algesic, vasoconstrictor substance (0.3 ml of autologous blood) or a pro-inflammatory molecule, carrageenin (1 mg in 0.1 ml saline) into the cisterna magna of pentobarbitone-anaesthetized Sprague-Dawley rats and was visualized in serial sections (50gLm) by use of a polyclonal antiserum.2 As previously rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(74 citation statements)
references
References 28 publications
3
70
0
1
Order By: Relevance
“…CP 93,129 at this dose signi®cantly reduced the neurogenic plasma extravasation in the dura mater encephali of the rat (Matsubara et al, 1991) which is known to depend on the activation of NK-1 receptors by substance P and (possibly) neurokinin A (Markowitz et al, 1987;Buzzi & Moskowitz, 1990). CP 93,129 at this dose also reduced the c-fos expression in the spinal trigeminal nucleus of the rat evoked by injection of autologous blood into the cisterna magna as a noxious stimulus (Nozaki et al, 1992). In the present study there was no enhancement of the release of ir-SP in the medullary brain stem following acidic stimulation after pretreatment with CP 93,129 at this dose.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…CP 93,129 at this dose signi®cantly reduced the neurogenic plasma extravasation in the dura mater encephali of the rat (Matsubara et al, 1991) which is known to depend on the activation of NK-1 receptors by substance P and (possibly) neurokinin A (Markowitz et al, 1987;Buzzi & Moskowitz, 1990). CP 93,129 at this dose also reduced the c-fos expression in the spinal trigeminal nucleus of the rat evoked by injection of autologous blood into the cisterna magna as a noxious stimulus (Nozaki et al, 1992). In the present study there was no enhancement of the release of ir-SP in the medullary brain stem following acidic stimulation after pretreatment with CP 93,129 at this dose.…”
Section: Discussionmentioning
confidence: 86%
“…An increase in c-fos expression was observed in the spinal trigeminal nucleus following noxious stimulation of the cranial meninges (Cutrer et al, 1995;Kaube et al, 1993;Nozaki et al, 1992). Substance P, which may be released in the trigeminal nucleus upon meningeal stimulation, possibly contributes to these nociceptive responses.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The inhibition of c-fos antigen expression within this brain region was previously demonstrated after giving analgesics such as morphine, or after sumatriptan or dihydroergotamine following noxious meningeal stimulation (Presley et al, 1990;Nozaki et al, 1992;Moskowitz et al, 1993 67580 and RPR 100893 are structural analogues, the possibility that RPR 100893 possesses local anaesthetic-like actions in addition to actions at the NKI receptor cannot now be ruled out. However, the large concentrations of RP 67580 required to achieve non-specific blockade argues in favour of an NKI receptor-mediated mechanism in the studies reported herein.…”
Section: Introductionmentioning
confidence: 99%